Linguistic Analysis Of Instructional Clarity In Students' Sports Demonstration Videos - Sianipar, Rimma (JR-ELT (Journal of Research in English Language Teaching), 2025)
This research examines the instructional clarity of demonstration sports videos produced by first-semester students in the Department of Physical Education, Health, and Recreation at Universitas Negeri Makassar. Three major areas are researched: sentence construction, word choice, and verbal and motor synchrony. Data were gathered from 10 student videos, transcribed, and analyzed through qualitative-descriptive procedures. The results indicate that most of the students used correct imperative sentences, but others struggled to structure clear and coherent directions. On the vocabulary side, most of the students used correct sports terminology, but others went wrong by using too general or imprecise terms. Further, while generally successful synchronization of verbal instructions with movements, there were some instances that showed inconsistency between the issued commands and carried-out actions. These findings suggest that although students already possess basic instructional communication proficiency in English, there is a need for further training to enhance the instructional performance of their sports demonstrations.